Seminal Plasma Lipidomics Profiling to Identify Signatures of Kallmann Syndrome - Li, Xiaogang; Wang, Xi; Li, Haolong; Li, Yongzhe; Guo, Ye (Frontiers in Endocrinology, 2021)
Background: Kallmann syndrome (KS) is a rare disease of developmental disorders. Our previous metabolomics work showed that linoleic acid and glycerophospholipids metabolism changed a lot in the KS. Here, we performed targeted lipidomics to further identify the different lipids species in KS. Methods: Twenty-one KS patients (treatment group) and twenty-two age-matched healthy controls (HC, control group) were enrolled. The seminal plasma and medical records were collected. Targeted lipidomics analysis of these samples was performed using UPLC-QTOF-MS method. Results: Lipidomics profiling of KS patients and HC are clearly separated in the orthogonal projections to latent structures- discriminant analysis (OPLS-DA). There are many differential lipids and the main different lipid species are TAG and PE. Conclusions: The lipidomics profile of KS patients changed. TAG, PC and PE are promising biomarkers for KS diagnosis. To our knowledge, this is the first report analyzing lipidomics in men with kallmann syndrome.